Synthesis of bis(imino)pyridine iron amide and ammonia compounds from an N-H transfer agent - Bowman, A. C.; Bart, Suzanne C.; Heinemann, Frank Wilhelm; Meyer, Karsten; Chirik, P. J. (Inorganic Chemistry, 2009)
Addition of the [NH] transfer reagent Hdbabh (dbabh = 2,3:5,6-dibenzo-7- azabicyelo[2.2.1]hepta-2,5-diene) to the bis(imino)pyr-idine iron bis(dinitrogen) complex, ( PDI)Fe(N ) ( PDI = 2,6-(2,6 Pr C H N=CMe) C H N), furnished the corresponding iron amide and ammonia compounds, resulting from cleavage of the strained amine. Isotopic labeling studies support N-H bond activation by a transient, parent imide, [( PDI)FeNH]. © 2009 American Chemical Society.